The Identity of Objects: Form & Nature in Digital Museums - Jason T Hewitt (tripleC: Communication, Capitalism & Critique)
Reconciling Justus Buchler's theory of natural complexes with the Peircean triadic categorial schema, a theory of semiotic radiance is articulated that elaborates the nature of identity with regard to informatic control over objects in a mu- seum collection. The model is deployed in the context of Edwina Taborsky's description of the historical transformation of the cultural syntax of museums. It is argued that the pattern of transformation is not random, but rather follows a specific and recognizable pattern. This pattern is consistent with a general trend in culture, identified by Heidegger, that becomes particularly problematic in its later stages. A theory of the commons derived from Hardt and Negri is articulated that looks to regenerate the space of the museum with regard to its informatic structures in order to renegotiate humanism in terms of a liberation ethic. The rubric of fundamental informatics is borrowed from Toru Nishigaki to describe the inquiry that pursues that end.